Casting out anger: stress, possession and the everyday in Taita, Kenya - Mahone, S (Duke University Press, 2024)
In 1955, Canadian psychiatrist Edward Margetts arrived in Kenya to take up the post of Chief Psychiatrist at Mathari Mental Hospital in Nairobi. Upon his arrival, the doctor was invited most urgently to Taita District with numerous reports and letters indicating that district officers had never seen such high levels of ‘hysteria’ anywhere in Kenya as they had in Taita. The inexplicable presence of disturbed behaviour, outbursts of violence, and general mental disorder was beginning to worry the local government. Margetts agreed to visit Taita but insisted he would forego a tour of the hospital. Instead, prompted by recent reports by anthropologists, he attended Taita possession ceremonies known as pepo and both photographed and interviewed participants. Within a few years of each other, the psychiatrist Margetts and anthropologist Grace Harris both wrote reports describing the ubiquity of objects within the pepo tradition noting that while dances incorporated props such as whistles, whiskey bottles, or a red fez, hysterical states were seemingly triggered by the appearance of ‘foreign’ objects such as cigarettes, motor cars, or the sounds of a match being struck. This paper places this discussion of WaTaita ‘stress’ within the context of worried outsider reporting that conflated the languages of anthropology, religion, and psychology amidst local explanations describing the anxiety and coping mechanisms of everyday modern life.